Effects of litter exposure and flock age of broiler breeders on hatchability and the microbial composition of eggshells, egg membranes, and egg contents - Csitári, Gábor; Such, Nikoletta; Menyhárt, László; Schermann, Kornél; Humpok, Kornél; Farkas, Valéria; Pál, László; Dublecz, Károly (Frontiers in Veterinary Science, 2025)
Floor eggs represent a significant loss for broiler breeder farms and hatcheries due to the increased risk of bacterial contamination of embryos, the hatchery environment, and newly hatched chicks. In this trial, the effects of litter exposure duration (3, 6, and 16 h) and breeder flock age (22–23 weeks vs. 65–66 weeks) were evaluated in terms of hatchability and the microbial composition of different egg components (eggshell, egg membrane, and egg content). The number of total culturable aerobic microbes on the eggshell surface increased following litter exposure and decreased after 3 h. Hatchability, however, was significantly reduced only after 16 h of exposure, primarily due to increased embryonic mortality. Litter exposure and flock age led to significant differences in microbiota composition, but only on the eggshell surface. At the phylum level, 16 h of litter exposure significantly increased the abundance of Firmicutes and decreased that of Proteobacteria. At the genus level, litter exposure resulted in increased relative abundances of Lactobacillus and Ruminococcus torques group and a decreased abundance of Staphylococcus. The microbiota of the egg membrane and egg content were similar at the phylum level; however, notable differences were observed at the genus level. Pseudomonas was dominant in the egg membrane but underrepresented in the egg content, leading to a significantly higher abundance of spoilage-associated bacterial genera in the membrane than in the content. Interestingly, the genus Flexivirga (phylum Actinobacteria) was detected in high abundance in both the egg membrane and egg content, despite not having been previously reported inside eggs. According to the results, no measurable bacterial translocation from the litter into the internal egg structures was observed. However, the frequency of floor egg collection may represent a critical factor if such eggs are intended for hatching.